Ex vivo detection of cadmium‐induced renal damage by using confocal Raman spectroscopy. Issue 12 (2nd September 2019) - Shen, Rong; Li, Yuee; Yu, Linghui; Wu, Haining; Cui, Rong; Liu, Sha; Song, Yanfeng; Wang, Degui
Abstract: Cadmium (Cd) is a toxic heavy metal which is harmful to environment and organisms. The reabsorption of Cd in kidney leads it to be the main damaged organ in animals under the Cd exposure. In this work, we applied confocal Raman spectroscopy to map the pathological changes in situ in normal and Cd‐exposed mice kidney. The renal tissue from Cd‐exposed group displayed a remarkable decreasing in the intensity of typical peaks related to mitochondria, DNA, proteins and lipids. On the contrary, the peaks of collagen in Cd‐exposed group elevated significantly. The components in each tissue were identified and distinguished by principal component analysis. Furthermore, all the biological investigations in this study were consistent with the Raman spectrum detection, which revealed the progression and degree of lesion induced by Cd. The confocal Raman spectroscopy provides a new perspective for in situ monitoring of substances changes in tissues, which exhibits more comprehensive understanding of the pathogenic mechanisms of heavy metals in molecular toxicology. Abstract : Raman spectrum is gradually used in pathological discrimination in various experimental models of cells or tissues. This study applied confocal Raman spectroscopy to map the pathological changes in situ in normal and Cd‐exposed mice kidney. This method provides a new perspective for in situ monitoring of substances changes in tissues, which exhibits more comprehensive understanding of the pathogenic mechanisms of heavy metals in molecular toxicology.